Thermal Investigation of a Solar Collector Using an Efficient Computational Technique - S. E. Ghasemi; J. Vahidi (Engineering Reports)
ABSTRACT The thermal efficiency of a flat‐plate solar collector is theoretically analyzed in this study. For this purpose, a novel computational technique called the Akbari‐Ganji method (AGM) is applied. The solution function derived using this method is examined for three different cases, including four‐term, six‐term, and eight‐term approximations. To validate the proposed method, the obtained results are compared with those from a published work, showing very good agreement. The thermal efficiency of the collector is comprehensively assessed under the influence of collector length, effectiveness coefficient, and heat loss coefficient. The results reveal that an increase in the effectiveness coefficient enhances the collector's thermal efficiency.